2018
DOI: 10.4314/gjass.v16i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cost efficiency of rainfed maize production in Yola North and Yola South Local Government Areas of Adamawa State, Nigeria

Abstract: This study analyzed the allocative (cost) efficiency of rainfed maize production in Yola North and Yola South Local Government Areas of Adamawa State, Nigeria. Purposive and simple random sampling techniques were used to select 128 respondents. The data collected were analyzed using descriptive statistics and stochastic frontier cost function model. Results revealed that the respondents had a mean age of 39 years and have large household sizes. The sampled farmers are experienced and cultivated an average of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…The significant of maize output value, cost of labour, cost of fertilizers, cost of maize seeds and cost of transportation at 1% level of probability implies that these are the most critical factors affecting the total cost of production in the study area. This result is in agreement with the works of Abdul M et al [1] and Ogundari K et al [6]. Abdul M et al [1], reported a gamma value of 0.8286 and all the parameters measured for cost efficiency were positively signed.…”
Section: Cobb-douglas Stochastic Frontier Cost Function Estimatessupporting
confidence: 92%
See 4 more Smart Citations
“…The significant of maize output value, cost of labour, cost of fertilizers, cost of maize seeds and cost of transportation at 1% level of probability implies that these are the most critical factors affecting the total cost of production in the study area. This result is in agreement with the works of Abdul M et al [1] and Ogundari K et al [6]. Abdul M et al [1], reported a gamma value of 0.8286 and all the parameters measured for cost efficiency were positively signed.…”
Section: Cobb-douglas Stochastic Frontier Cost Function Estimatessupporting
confidence: 92%
“…This result is in agreement with the works of Abdul M et al [1] and Ogundari K et al [6]. Abdul M et al [1], reported a gamma value of 0.8286 and all the parameters measured for cost efficiency were positively signed. Similarly, Ogundari K [6], obtained a gamma value of 0.805 and all the parameters measured were positively signed.…”
Section: Cobb-douglas Stochastic Frontier Cost Function Estimatessupporting
confidence: 92%
See 3 more Smart Citations